2021
DOI: 10.1021/acs.jpcb.1c08570
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Modulation by Ultrafast Chromophore Twisting Events: Developing a Powerful Toolset for Fluorescent-Protein-Based Imaging

Abstract: The advancement of modern life sciences has benefited tremendously from the discovery and development of fluorescent proteins (FPs), widely expressed in live cells to track a myriad of cellular events. The chromophores of various FPs can undergo many ultrafast photophysical and/or photochemical processes in the electronic excited state and emit fluorescence with different colors. However, the chromophore becomes essentially nonfluorescent in solution environment due to its intrinsic twisting capability upon ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…37 Interestingly, many of the I-ring (i.e., middle ring between P-ring and FI-ring, see Figure 1a) mode frequencies remain largely constant between the FPs studied, consistent with the proteinanchoring role of the I-ring with much less flexibility. 37,44…”
Section: Revealing the Local-environmentinduced Changes To Vibrationa...mentioning
confidence: 99%
“…37 Interestingly, many of the I-ring (i.e., middle ring between P-ring and FI-ring, see Figure 1a) mode frequencies remain largely constant between the FPs studied, consistent with the proteinanchoring role of the I-ring with much less flexibility. 37,44…”
Section: Revealing the Local-environmentinduced Changes To Vibrationa...mentioning
confidence: 99%
“…The exact twisting coordinates (dihedral angles, one-bond flip, or hula twist) and geometries and whether intermediate states are involved remain elusive for most RSFPs [ 36 , 37 , 38 ]. Studies on photoisomerization events have been a hot topic for the HBDI chromophore and its derivatives in solution, but the gained knowledge cannot be directly transferred into a chromophore in the protein matrix due to the complex electrostatic and steric interactions between the chromophore and surrounding protein residues, which are intrinsically more heterogeneous and asymmetric than the solution environment [ 39 , 40 , 41 , 42 ]. Therefore, it is urgent and necessary to elucidate the detailed structural motions of the chromophore and local amino acids in the electronically excited and “hot” (non-equilibrium) ground states, which are essential for the deepened understanding and rational development of next-generation RSFPs [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The structure and dynamics of the chromophore environment are obviously critical for controlling ultrafast dynamics which lead to nonradiative decay of the excited state, thus limiting the fluorescence quantum yield. In most bright red FPs (RFPs), the chromophore occupies a cis -phenolate conformation in the ground state with the phenolate exhibiting a single-bond character and the negative charge localized on the O atom of the phenol moiety. , Many recent studies have identified the rotation of the chromophore’s P-bond as a primary pathway of ultrafast nonradiative decay. , For example, in mCherry-like FPs, Drobhizev and co-workers examined the roles of several side chains near the MYG chromophore in restricting access to twisted intramolecular charge transfer (TICT) states through phenolate-bond (P-Bond) rotation . The presence of these TICT states permits ultrafast nonradiative decay through a conical intersection seam on the excited state surface.…”
Section: Introductionmentioning
confidence: 99%